A hybrid price-based demand response program for the residential micro-grid. (15th October 2019) - Monfared, Houman Jamshidi; Ghasemi, Ahmad; Loni, Abdolah; Marzband, Mousa
Abstract: During the past two decades, providing solutions to enhance the efficiency of power systems, like optimal consumption management has been attracting a good deal of attention. Demand Response (DR) programs, have always been among the appropriate ways to persuade consumers to alter consumption patterns. In the main, the implementation of DR programs is carried out by price-based and incentive-based strategies. In this paper, first, a brief overview of the smart grid principles on retail electricity pricing is presented. Then, a hybrid price-based demand response (HPDR) is proposed, which is more adaptable to pricing principles compared to other existing strategies. This strategy is implemented in day-ahead scheduling of a residential microgrid. Moreover, to increase the accuracy of the proposed model, the uncertainty regarding decision variables and parameters including the generation units, load dispatch in the Micro-grid is considered. Finally, the results of numerical studies show the effectiveness of the proposed retail pricing strategy, and demonstrate a decrease in Peak-to-Valley (PtV) index and Coefficient of Variation Percentage (CVP) by almost 12% and 25% as well as an increase in social welfare indicator, power sale at peak times, respectively, by approximately 18%, 24%, and 25% in comparison with other methods. Highlights: A new hybrid priced-based demand response program has been proposed. A new social acceptability index called simplicity has been introduced. The uncertainty associated with decision variables has been considered.